On θ-generalized closed sets - Julian Dontchev; Haruo Maki (International Journal of Mathematics and Mathematical Sciences)
The aim of this paper is to study the class of θ-generalized closed sets, which is properly placed between the classes of generalized closed and θ-closed sets. Furthermore, generalized Λ-sets [16] are extended to θ-generalized Λ-sets and R0-, T1/2- and T1-spaces are characterized. The relations with other notions directly or indirectly connected with generalized closed sets are investigated. The notion of TGO-connectedness is introduced.